An examination of mediating mechanisms in the relationship between intellectual capital, good corporate governance, and firm performance - Riswandari, Ernie; Zarkasyi, Wahyudin; Suharman, Harry; Dahlan, Muhammad (Business: Theory and Practice, 2026)
Increased competition in the industry is a result of globalization, which brings both challenges and opportunities for all parties involved. The expansion of the business sector and ease of market entry have made competition even fiercer, leading to more competitive prices. Companies are working hard to maintain their operations in the face of this competitive pressure. This study to examine the role of the value chain on intellectual capital (IC) and good corporate governance (GCG). Previous research has shown inconsistencies whereby companies with well-managed resources have not demonstrated improved performance. This study aims to address this issue in order to improve corporate performance and provide a new perspective on the role of intermediaries in the value chain. This quantitative research using the explanatory method. data collection techniques using purposive sampling method from manufacturing companies located in Indonesia. The collected data were analyzed with Partial Least Squares (PLS) to conduct multiple regression tests. The results of hypothesis testing show that IC has a positive impact on the company’s performance through the value chain. GCG has been shown to have no positive impact on the company’s performance, except through the value chain. The implications of the research results for manufacturing companies include improving IC quality by continuing training for human resource skills, improving resource development facilities, strengthening cooperation with suppliers for smooth production, and improving relationships with consumers so that products are more accepted. The principles of Good Corporate Governance (GCG) form the foundation for establishing systems, structures and a corporate culture that can adapt to business changes and support internal control and risk management. For GCG to be implemented in accordance with best practice, a strong commitment is required at all levels of the organisation, from the lowest to the highest levels of management. This study aims to provide a new perspective on the intermediate position in the value chain by expanding the Resource Base View (RBV) theory through data on the influence of IC and strong corporate governance on company success.